Seasonal synchronization of seed release phenology promotes long‐distance seed dispersal by wind for tree species with medium wind dispersal potential. (8th June 2015) - Heydel, Felix; Cunze, Sarah; Bernhardt‐Römermann, Markus; Tackenberg, Oliver; Bruun, Hans Henrik
Abstract Questions How does the seasonal variability of wind affect the seed release phenology of plant species from different vegetation types? Do wind‐dispersed species show a seasonal synchronization of seed release timing with meteorological conditions that promote long‐distance dispersal (LDD) by wind? Location Germany, Central Europe. Methods We combined empirical observations of seed release phenology with simulations of LDD by wind. We simulated LDD by wind for species differing in seed terminal velocity for open and forested habitats using a broad set of measured meteorological conditions. In order to investigate the extent of seasonal synchronization of seed release with LDD, we compared species' LDD throughout the year with phenological data on timing of seed release for herbaceous species from open and tree species from forested habitats. Results For tree species with winged seeds and medium seed terminal velocity (e.g. Acer platanoides, Tilia cordata) we found a pronounced seasonal synchronization of seed release timing with high LDD by wind. These species showed an extended ripening duration together with both the highest rate of seed release and high LDD in winter. Species with low seed terminal velocity (i.e. high wind dispersal potential) from open habitats (mainly species from the Asteraceae with plumed seeds) and forested habitats (e.g. tree species of the genera Populus, Salix) both showed high LDD but lacked seasonal synchronization of seed release timing with LDD. Conclusions For forest species with medium seed terminal velocity, the seasonal timing of seed release during winter and strong winds could be evidence for phenological adaptations to timing of wind dispersal within periods with favourable conditions. Our finding that species with low seed terminal velocity and high LDD throughout the year did not show seasonal seed release synchronization tentatively suggests that selection for other mechanisms such as synchronization with short‐term weather events might promote LDD of these species. Our results provide insights into how seasonal seed release timing of plant species from different vegetation types affects LDD by wind and shows that seed release phenology should be considered while assessing species' wind dispersal potential.